Finland's economic relations with developing countries, including development cooperation, in the 1990s - Suomi. Ulkoasiainministeriö; Suomi. Ulkoasiainministeriö. Kehitysyhteistyöosasto (Ministry for Foreign Affairs of Finland, Finnish Development Agency, 1989)
Conclusions and recommendations (lehdet 21-24).
Keywords: kehitysapu; kehitysyhteistyö : Suomi; kansainväliset suhteet : Suomi : kehitysmaat